2020
DOI: 10.2991/efood.k.200824.001
|View full text |Cite|
|
Sign up to set email alerts
|

Citrus aurantifolia(Christm.) Swingle (lime) Fruit Extract Inhibits the Activities of Polyol Pathway Enzymes

Abstract: Diabetes mellitus is associated with several complications, which may result from one or more factors including increased flux of polyol pathway. This study evaluated the inhibitory potential of four citrus fruits namely Citrus paradisi Macfad. (grape), Citrus limon (L.) Osbeck (lemon), Citrus aurantifolia (Christm.) Swingle (lime) and Citrus sinensis (L.) Osbeck (orange), on the activities of aldose reductase and sorbitol dehydrogenase -the two enzymes that mediate the polyol pathway. This is determined by in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…This activity is associated with the presence of secondary metabolites found in the peel of C. aurantifolia. Kazeem et al (2020) [12] also showed that C. aurantifolia fruit could inhibit aldose reductase effectively with an IC 50 of 138.66 g/mL. Besides that, it can also inhibit sorbitol dehydroreductase with an IC 50 of 47.21 g/mL.…”
Section: Anti-inflammatorymentioning
confidence: 88%
See 1 more Smart Citation
“…This activity is associated with the presence of secondary metabolites found in the peel of C. aurantifolia. Kazeem et al (2020) [12] also showed that C. aurantifolia fruit could inhibit aldose reductase effectively with an IC 50 of 138.66 g/mL. Besides that, it can also inhibit sorbitol dehydroreductase with an IC 50 of 47.21 g/mL.…”
Section: Anti-inflammatorymentioning
confidence: 88%
“…Kinetic studies also show that the extract can competitively inhibit the activity of both enzymes. Enzyme inhibition through the polyol pathway is associated with the presence of flavonoids and limonoids in the C. aurantifolia [12].…”
Section: Anti-inflammatorymentioning
confidence: 99%
“…Swingle is nutrient-rich and effective as a pesticide, anti-oxidant, anti-bacterial, anti-cancer, and anti-inflammatory agent [9]. These various biological activities are caused by the secondary metabolite content found in lime, namely coumarins, alkaloids, flavonoids [10], limonoids, carotenoids, phenolics, terpenes [11], and essential oils [12]. Every part of lime has benefits, including the peel, which is said to be a good source of pectin, essential oils, and phenolic compounds [13].…”
Section: Introductionmentioning
confidence: 99%
“…However, the juice of lime fruit also has metabolites that have antioxidant activity. Lime juice contains several natural antioxidant compounds, such as flavonoids (hesperidin, rutin, didymin) and limonoids (limonin), as well as ascorbic acid (Vitamin C) (Kazeem et al, 2020)). Lime juice contains ascorbic acid from 21.8 g/100g to 38.9 g/100g, and seedless lime has lime juice 60-66% that contains ascorbic acid of 118.2 -140.8 mg/100g (Shrestha et al, 2012).…”
Section: Introductionmentioning
confidence: 99%